Possible Cases of SARS-CoV-2 Reinfection In Pekanbaru, Indonesia - Rahmat Azhari Kemal; Dewi Anggraini (Interna Publishing, 2022)
Confirmed and possible reinfection cases of SARS-CoV-2 have been reported from various countries. Here we present two cases of possible SARS-CoV-2 reinfection in Pekanbaru, Indonesia. A 26 years old female and a 27 years old male healthcare workers were first confirmed by PCR with high Ct-value (>35) while presenting no or mild symptoms, respectively. In more than one month since the last negative test results, both patients developed typical COVID-19 symptoms; fever and anosmia. RT-PCR results for SARS-CoV-2 were positive with Ct-value less than 30. The timeframe between 1st and 2nd episode, negative test result between episodes, and epidemiological risk factor strengthened the possibility of reinfection. However, we did not have whole genome sequence (WGS) or viral viability data to further confirm reinfection with different viable virus. The requirement of viral WGS data to confirm true reinfection cases calls for investment in whole genome sequencing platform in public health laboratories. We encourage standardized definition of SARS-CoV-2 reinfection case in order to be able to investigate and observe such cases.